Pelatihan Relaksasi Bumil Sehat untuk Menurunkan Kecemasan Ibu Hamil Risiko Tinggi - Libbie Annatagia; Sofia Retnowati (Universitas Islam Indonesia, 2011)
A growing body of research indicates that maternal anxiety is a significant risk factor for adverse pregnancy and birth outcome. This study evaluated the effectiveness of